Exploring the Correlates of Individual Willingness to Engage in Ideologically Motivated Cyberattacks. Issue 3 (4th March 2017) - Holt, Thomas J.; Kilger, Max; Chiang, Lichun; Yang, Chu-Sing
ABSTRACT: In the last few years, there has been an increase in the use of Web defacements, where individuals post political or ideological messages on websites in place of the original content. There is generally little research on the predictors of Web defacements against either domestic or foreign targets. This study addresses this gap by examining the attitudinal and behavioral correlates of willingness to engage in defacements using a sample of university students in Taiwan and the United States. The findings demonstrate that political attitudes toward marginalized groups and support for cybercrime increase individuals' willingness to engage in defacements.